2021
DOI: 10.1080/00380253.2021.1886618
|View full text |Cite
|
Sign up to set email alerts
|

Crafting the Conditions for Professional Membership: Women of Color Navigating Inclusion into Academia

Abstract: Previous scholarship has documented women of color's experiences in professions such as law and medicine, but less research has explored how women of color experience the process of becoming members of professions. Using academia as a case I draw from interviews with thirty women at a single research-intensive university to demonstrate that women of color have different orientations to professional membership as compared to white women. These differences are made evident by women of color's extra work to justi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Second, we also do not want to imply that we are, independently or collectively, the best examples of what it means to treat others with empathy, respect, and inclusion within our community. Rather, our intention is merely to share some observations and experiences as we continue our journeys that may inform current discussions about inclusiveness within our community (see also Avery et al, 2022;Brown & Ramlackhan, 2021;Hideg, DeCelles, & Tihanyi, 2020;Johnston, 2019;Montgomery, 2021;Ward, 2021). Third, even though large-scale changes are likely necessary, we suggest that collectively engaging in relatively small acts of empathy and respect may also allow us to enhance inclusion of ideas and scholars.…”
Section: From the Editors Insights On How We Try To Show Empathy Resp...mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we also do not want to imply that we are, independently or collectively, the best examples of what it means to treat others with empathy, respect, and inclusion within our community. Rather, our intention is merely to share some observations and experiences as we continue our journeys that may inform current discussions about inclusiveness within our community (see also Avery et al, 2022;Brown & Ramlackhan, 2021;Hideg, DeCelles, & Tihanyi, 2020;Johnston, 2019;Montgomery, 2021;Ward, 2021). Third, even though large-scale changes are likely necessary, we suggest that collectively engaging in relatively small acts of empathy and respect may also allow us to enhance inclusion of ideas and scholars.…”
Section: From the Editors Insights On How We Try To Show Empathy Resp...mentioning
confidence: 99%
“…We hope that these ideas and the important discussions that have come before (e.g., Avery et al, 2022;Brown & Ramlackhan, 2021;Hideg et al, 2020;Johnston, 2019;Montgomery, 2021;Ward, 2021) and those that will come after have the potential to expand access to authors and reviewers of AMJ, and, in doing so, to address these research questions that are, to date, less examined in our literature.…”
Section: Elizabeth E Umphress University Of Washingtonmentioning
confidence: 99%
“…Class distinctions become shrouded through the assumption that academics occupy a shared class background due to either a continuation of their class background or social mobility gained through educational status (Haney 2015; Lee 2017; Lee and Maynard 2017). Literature on faculty experiences has demonstrated that class background can remain salient throughout one’s career, thereby challenging the notion that completing a terminal degree removes any potential class-based barriers and places all academics on equal footing (Haney 2015; Lee 2017; Morgan et al 2022; Ward 2022).…”
Section: Documented and Perceived Deficits Among Fgwc Individualsmentioning
confidence: 99%
“…Ward (2022) finds that women of color describe engaging in significant extra work to facilitate membership into academia compared to White women. Strategies used by the participants in Ward’s (2022) study included trying to appear less “emotional” and “passionate” about their academic interests and periodically not attending academic gatherings to avoid potential discrimination. In general, much of the extra work done by women of color resulted from an “expressed incongruity between who they were as people as opposed to themselves as professionals” (Ward 2022:502).…”
Section: Documented and Perceived Deficits Among Fgwc Individualsmentioning
confidence: 99%
See 1 more Smart Citation